Volatile Organic Compounds from Native Potato-associated Pseudomonas as Potential Anti-oomycete Agents - De Vrieze, Mout; Pandey, Piyush; Bucheli, Thomas D.; Varadarajan, Adithi R.; Ahrens, Christian H.; Weisskopf, Laure; Bailly, Aurélien (Frontiers in Microbiology, 2015)
The plant kingdom represents a prominent biodiversity island for microbes that associate with the below- or aboveground organs of vegetal species. Both the root and the leaf represent interfaces where dynamic biological interactions influence plant life. Beside well-studied communication strategies based on soluble compounds and protein effectors, bacteria were recently shown to interact both with host plants and other microbial species through the emissions of volatile organic compounds (VOCs). Focusing on the potato late blight-causing agent Phytophthora infestans, this work addresses the potential role of the bacterial volatilome in suppressing plant diseases. In a previous study, we isolated and identified a large collection of strains with anti-Phytophthora potential from both the phyllosphere and the rhizosphere of potato. Here we report the characterization and quantification of their emissions of biogenic volatiles, comparing 16 Pseudomonas strains differing in i) origin of isolation (phyllosphere vs. rhizosphere), ii) in vitro inhibition of P. infestans growth and sporulation behavior, and iii) protective effects against late blight on potato leaf discs. We systematically tested the pharmacological inhibitory activity of core and strain-specific single compounds against P. infestans mycelial growth and sporangial behavior in order to identify key effective candidate molecules present in the complex natural VOCs blends. We envisage the plant bacterial microbiome as a reservoir for functional VOCs and establish the basis for finding the primary enzymatic toolset that enables the production of active components of the volatile bouquet in plant-associated bacteria. Comprehension of these functional interspecies interactions will open perspectives for the sustainable control of plant diseases in forthcoming agriculture.